Cenozoic Age Counterclockwise Rotation in the Northwest End of the Sierras Pampeanas, Argentina - Gutierrez, Adolfo Antonio (2023)
Investigations into the Andean orocline revealed a counterclockwise rotation of about 37° in the north and a clockwise rotation of about 29° in the south. This rotation would have started in the Eocene because the Nazca and South American plates converged. The transition zone between the Puna and the Sierras Pampeanas has a clockwise rotation pattern. Our new data show that the NE convergence of the Nazca and South American plates caused the counterclockwise rotation around the NW end of the Sierras Pampeanas. The temperature rise during a magmatic activity at 13 Ma would have favored a counterclockwise rotation of the mountain blocks of about 20° on a detachment zone within 10 to 15 km of depth. These range rotations generated local stress tensors trending NE and NW, facilitating the development of valleys, basins, mineralized dikes, mineral deposits, and alluvial fans separated from their origin. The Atajo fault shows both ductile and brittle characteristics. A mylonitic belt from the Sierra de Aconquija was juxtaposed on the rocks of the Ovejería Block and the Farallón Negro Volcanic Complex by reverse vertical displacement, and a dextral horizontal component of displacement resulted in curvatures that gave rise to pull-apart basins and step over features. The Santa Maria Valley, Campo del Arenal, Hualfín Valley, and Pipanaco salt flat most likely constituted a vast early Miocene basin rarely interrupted by low feature relief.